The Effect of Advertising, Image, Brand Trust, and Price on Interest to Buy Nescafe Ready-to-Drink Coffee in Perlabian Village - Mhd Hadi Wibowo; Zulkifli Musannip Efendi Siregar; Mulya Rafika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Purchase intention is a response or an effective process when liking a product. Purchase intention is influenced by advertising, brand image, trust, and product prices. This study aims to determine the effect of advertising, brand image, trust, and price on buying intention of ready-to-drink Nescafe coffee in Perlabian Village. The method used in this study is a quantitative method by collecting data using a questionnaire instrument. The population in this study is the Perlabian Village community. Determination of the sample using a non-probability sampling method with a purposive sampling technique in order to obtain a sample of 100 respondents. Data was obtained from the results of a questionnaire using the Google form. Data were analyzed using instrument testing techniques (validity and reliability tests), linear regression tests, classical assumption tests (normality and heteroscedasticity), and hypothesis testing (coefficient of determination) using SPSS. The results showed that the simultaneous variables of advertising, brand image, brand trust, and product prices have a significant effect on purchase intention. Meanwhile, partially, only advertising, brand trust, and product prices have a significant effect on the intention to buy Nescafe ready-to-drink coffee in Perlabian Village, while the brand image variable has no effect. Companies need to improve the brand image owned by ready-to-drink Nescafe products, especially for the people of Perlabian Village so that people make ready-to-drink Nescafe products their first choice.